Development of Statistical Physics Teaching Materials Based on Three Levels of Representation to Improve Mental Models - Hazrati Ashel; Ida Hamidah; Sjaeful Anwar; Muslim Muslim (UIN Fatmawati Sukarno Bengkulu, 2025)
This research aims to produce Statistical Physics teaching materials based on three levels of representation to improve mental models. To achieve this goal, the research design used is Design and Development Research (DDR) which consists of three stages, namely development, validation, and implementation. At the stage of developing teaching materials, the 4STMD method is used which consists of the stages of selection, structuring, characterization, and didactic reduction. This research is limited to the selection and structuring stages. The instruments used are a review sheet of suitability of each aspect, a validation sheet, and a practicality questionnaire. The data obtained were analyzed using CVR and PCM. Based on the results of data analysis, it was obtained that the teaching materials was in accordance with the indicators, concept labels, substance context, and pedagogical context. The teaching materials developed are valid and practical to use. Teaching materials can also improve students' mental models. Researchers recommend using this teaching material in Statistical Physics lectures to improve students' mental models.